ECO(RE)EXISTÊNCIA: o elemento natural como expressão da força e do gesto político na arte de Frans Krajcberg - Tome, Maria Marta Morra (2020)
Frans Krajcberg (Poland, 1921-Brazil, 2017) was an exponential artist and his original and sui generis art maintained his indignation as a leitmotiv - he lived in disagreement with the destruction of nature, acting as an environmentalist / ecologist. This